PENGEMBANGAN PETA KECEPATAN GELOMBANG GESER DAN PETA TAHANAN PENETRASI STANDAR DI SEMARANG - Abi Shandy Jananda; Pratami Fadillah; Windu Partono; Siti Hardiyati (Jurnal Karya Teknik Sipil, 2014)
To perform the necessary analysis of wave propagation subsurface soil data are complete and accurate. Data were obtained directly from the field geotechnical surveys and obtained from laboratory tests on soil samples taken from beneath the surface through bore hole. Dynamic soil properties determined indirectly from the results of static testing in the field, the Standard Penetration Test (SPT) and Cone Penetration Test (CPT). Several researchers have conducted studies and generate empirical correlation between shear wave velocity (vs) with SPT N-values and CPT cone resistance (qc) such as Imai (1977), Imai & Tenouchi (1982), Ohta & Goto (1978), and Sykora & Stokoe (1983). Using data from the soil investigation reports of 85 locations spread across the Semarang city, consisting of 156 boring point, 83 point manual CPT, and 96 points machine CPT. To determine the site class parameters using weighted average method of N and vs value for 30 meters topsoil profile. The results of this study become soil properties map ( QUOTE   and  QUOTE  ), and site-class map of Semarang city. Based on two (2) soil properties, soil classification in Semarang divided into two site-class, stiff soil (SD) and soft soil (SE). SE site-class commonly found in the north coast side of Semarang city, while soil SD site-class found in the south side of Semarang city.